Study on traffic simulation to control signalized junction - Xiong, Ying Qi (2017)
In Singapore, traffic congestion and high occurrence of accidents at junctions are problems that have become more severe nowadays in the central areas. Traffic signal management is recognized as one of the most efficient ways to improve urban network congestion. It involved in planning, designing and maintenance of a traffic signal system in order to achieve a better road environment, safe and reliable signalized junction operations. Various signal control strategies have been proposed and implemented in many countries in the world in the past decades, and the results show great improvement in the traffic conditions. This study’s focus is on the simulation of a traffic model, Cell Transmission Model (CTM) which was programmed through Visual Basic for Applications (VBA). A cross-junction positioned at the central area of Singapore was chosen for this simulation. The road length and road speed between junctions are short and low respectively and most of them are one-way traffic. Therefore, this signalized cross-junction was designed with short road length, low vehicle speeds and one- way traffic in both horizontal and vertical direction of traffic. The roads located before and after the junction were broke into many equal length cells which were introduced in the study of CTM that would be explained in detail in the next few chapters. Various traffic signal timings were designed and each respective timing would be run though the program of VBA to obtain the sum of the travel time of all vehicles in the cells in both the horizontal and vertical direction of traffic. The result is to obtain a best designed traffic signal timing from the graph produced using the sum of travel time of all vehicles and different signal timings. Therefore, the aim of this study is to achieve a minimum vehicle travel time with the best suitable traffic signal timings.